Teaching Factory Management to Improve the Employability of Vocational High School Graduates (A Case Study at SMK Negeri 8 Bandung and SMK Negeri 2 Cimahi) - Edwar Setiawan; Waska Warta (CV. Media Digital Publikasi Indonesia, 2026)
This study analyzes the implementation of Teaching Factory (TeFa) management as a strategic instrument to increase the labor-market absorption of graduates of Vocational High Schools (SMK) in West Java, Indonesia. Although TeFa has been nationally mandated, the relatively high unemployment rate among SMK graduates in the province—12.42% in February 2025—indicates that many schools have not yet managed the program in an integrated, industry-oriented manner [5]. Using a qualitative approach and a comparative case study design, this research examines management practices at SMK Negeri 8 Bandung and SMK Negeri 2 Cimahi, both of which are regarded as information-rich cases. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that both schools implement TeFa using George R. Terry’s four management functions—planning, organizing, actuating, and controlling—although with different emphases. Planning is carried out through curriculum alignment and business-plan formulation in collaboration with industry partners. Organizing simulates real industrial work environments, complete with role distribution, job descriptions, and standardized student practice rooms. Actuating engages students in full production cycles, enabling them to acquire both technical and soft skills. Controlling is conducted through quality-control mechanisms, performance assessment, and follow-up programs, including tracer studies. The study concludes that a comprehensive and industry-linked Teaching Factory management model is a key factor in improving SMK graduates’ employability and competitiveness in the world of work.